Synthesis, growth, structural, optical, thermal and mechanical studies on cadmium nitrate p-nitrophenol: A semi-organic nonlinear optical application. (2021) - Chinnasamy, E.; Indumathi, N.; Hemalatha, A.; Venkatesan, A.; Raja Saravanan, M.E.; Uthrakumar, R.; Deepa, K.; Senthil, S.; Kaviyarasu, K.
Abstract: The semi-organic single crystal of Cadmium nitrate p-nitrophenol (CNPN) was successfully grown by the slow evaporation technique. The functional groups have identified by using Fourier transform infrared (FT-IR) spectral analysis. The optical transparency and band gap of grown crystals were measured from UV–Vis spectrum. The thermal stability of grown crystal has been analyzed by TG/DTA studies. Dielectric studies were measured for the crystal from 50 Hz to 5 MHz at room temperature. The second harmonic generation efficiency of 1.30 times that of KDP was measured using Kurtz Perry powder method.